ENTREPRENEURIAL ORIENTATION, ROLE OF THE GOVERNMENT, AND PARTNERSHIP ON MARKETING PERFORMANCE OF FURNITURE EXPORT SMES: A STUDY ON FURNITURE EXPORT COMPANIES IN JEPARA - Samsul Arifin; Nurul Komaryatin (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Objective: The study is to analyze the role of the government, entrepreneurial orientation and partnership on marketing performance in the Jepara furniture industry. The objects of the research are furniture export companies in Jepara. Research Design & Methods: The sample was 100 respondents and the sampling technique was the simple random sampling technique. The data analysis uses the PLS technique. Findings: The testing results using PLS illustrates that partnership on marketing performance shows the t value of 0.045974; entrepreneurial orientation on marketing performance shows the t value of 1.747034; while the role of the government on marketing performance shows the t value of 2.985408. The test results were compared using t tables of 1.66023. The results showed that the role of the government had a positive and significant effect on marketing performance seen from t value > t table. Entrepreneurial orientation also had a positive and significant effect on marketing performance obtained from t value > t table. However, the partnership had no significant effect on marketing performance since t value < t table. Implications & Recommendations: This study recommends that companies need to pay attention to entrepreneurial orientation and government policies because these two factors are significant determinants of company marketing performance. Increasing partnerships is also important to develop company progress. Contribution & Value Added: This research adds the theoretical contributions to marketing management. Practically, the results of this research can be utilized by furniture export companies to increase overseas sales.